Controllable degradation polylactic acid containing boric acid ester unit, preparation method and application
By introducing easily hydrolyzable borate ester units into the polylactic acid (PLA) molecular chain, the problem of uncontrollable PLA degradation rate is solved, enabling rapid degradation in alkaline environments. This makes it suitable for short-cycle environmentally friendly packaging and the biopharmaceutical field.
Patent Information
- Application Number
- CN202511205345.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-11-07
AI Technical Summary
The degradation rate of existing polylactic acid is uncontrollable, and traditional synthesis methods are cumbersome, lacking a simple and controllable method for preparing polylactic acid.
Easily hydrolyzable borate ester units are introduced into the polylactic acid (PLA) molecular chain. Diol monomers containing borate ester units are generated by reacting 1,4-phenylenediboric acid with triols containing 1,2-diol groups. Controlled degradable PLA is then prepared by isocyanate chain extension reaction.
In an alkaline environment, borate ester units are easily broken, which significantly accelerates the degradation rate of polylactic acid. The degradation rate can be controlled by adjusting the borate ester content, making it suitable for industrial production.
Smart Images

Figure CN120904441A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of biodegradable high molecular materials, and in particular to a controllable degradation polylactic acid containing borate units, a preparation method and application. BACKGROUND
[0002] With the development of society, the demand for plastics is increasing year by year. The plastic pollution (such as marine microplastics) caused by the use and abandonment of a large amount of traditional plastics has become a global concern. How to solve the plastic pollution is an important topic worthy of study. Developing biodegradable plastics to gradually replace traditional plastics is one of the effective ways to solve the plastic pollution. In the family of biodegradable plastics, polylactic acid (PLA) is considered to be the most promising and competitive member. Its monomer is fermented from starch and other sugars, and does not need to use petroleum as raw material, so it is an important biobased high molecular material. Polylactic acid is a relatively hard thermoplastic with high strength and modulus, and its physical properties are similar to those of polyethylene terephthalate and polystyrene.
[0003] Although polylactic acid can be biodegraded, it has the problems of slow environmental degradation rate and uncontrollable degradation rate. Studies on the degradation mechanism of polylactic acid show that the microbial degradation rate is 10 8 ~ 10 20 Therefore, the non-biological hydrolysis process of polylactic acid is the key step to determine its degradation rate (Adv. Sci. 2021, 8, 2001121). In view of this, introducing a “breakage unit” that is easy to break and quickly hydrolyzed into the macromolecular chain is a main strategy to regulate the degradation rate of polylactic acid. Under certain conditions, the “breakage unit” can break preferentially to the lactic acid ester group, causing the macromolecule to break quickly and thus accelerating the degradation of polylactic acid. For example, Wurm et al. introduced an easily degradable β-hydroxyl phosphate group “breakage unit” into the main chain of polylactic acid by ring-opening copolymerization of lactide with cyclic phosphate, realizing the controllable degradation of polylactic acid (J. Am. Chem. Soc. 2021, 143, 16673-16681). However, the current method of introducing “breakage units” into polylactic acid is usually through copolymerization of lactide with cyclic monomers, which has the problems of harsh synthesis conditions and complicated steps. Therefore, there is still a lack of a simple method for preparing controllable degradation polylactic acid. SUMMARY
[0004] In order to solve the problems of the prior art, the present application provides a controllable degradation polylactic acid containing borate units, a preparation method and application.
[0005] In order to solve the problems of the prior art, the present application provides the following technical solutions:
[0006] A controllable degradation polylactic acid containing borate units has the following structural formula:
[0007]
[0008] wherein a+b = 10-67, c = 2-6, d = 1-5, e = 2-25; R1 is one of the following groups:
[0009]
[0010] A method for preparing a controllable degradation polylactic acid containing borate units, comprising the following steps:
[0011] (1) First, 1,4-benzenediboronic acid and a triol compound containing 1,2-diol groups are dissolved in a solvent, then anhydrous magnesium sulfate is added, and the reaction is stirred at room temperature; Finally, the anhydrous magnesium sulfate is removed by suction filtration to obtain a filtrate, and the filtrate is dried to obtain a diol monomer containing borate units.
[0012] (2) The low molecular weight polylactic acid diol is added to the solvent and mixed, and is completely dissolved by heating under inert gas protection. The diisocyanate and the catalyst are separately diluted with a solvent and then added dropwise. After all the addition, the end-capping reaction is carried out under mechanical stirring and condensation reflux. Then, the diol monomer containing borate units synthesized in step (1) is added, and after chain extension, precipitation, washing and drying, a controllable degradation polylactic acid containing borate units is obtained.
[0013] Further, the structure of the triol compound containing 1,2-diol groups in step (1) is:
[0014] wherein n = 1-5.
[0015] Further, in step (1), the reaction time is 8-24h; the solvent is one or a combination of two or more of anhydrous tetrahydrofuran, methanol, ethanol; the molar ratio of 1,4-benzenediboronic acid to the triol compound containing 1,2-diol groups is 1:2-2.1.
[0016] Further, in step (2), the number average molecular weight of the low molecular weight polylactic acid diol is not more than 5000g·mol -1 .
[0017] Further, in step (2), the diisocyanate is one of isocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 4,4-methylene bis(isocyanate phenyl); the catalyst is dibutyltin dilaurate or stannous octoate, and the solvent is one or a combination of two or more of tetrahydrofuran, toluene, N,N-dimethylformamide, N,N-dimethylacetamide.
[0018] Further, the molar ratio of the low molecular weight polylactic acid diol, diisocyanate, borate unit-containing diol monomer, and catalyst in step (2) is 1:2-4.98:1-3.98:0.005-0.013.
[0019] Further, the reaction time of the end-capping is 1-2 h, the reaction temperature is 50-65 DEG C, the reaction temperature of the chain extension is 60-85 DEG C, and the reaction time is 2-6 h.
[0020] The controllably degradable polylactic acid containing borate units prepared by the above preparation method has a faster degradation rate than the degradation rate of polylactic acid with the same molecular weight in an alkaline environment with pH greater than or equal to 8, and the degradation rate increases with the increase of the borate content.
[0021] The controllably degradable polylactic acid containing borate units prepared by the above preparation method is applied in short-period environmental protection packaging, seed coating, and biomedical field.
[0022] The beneficial effects of the present application are:
[0023] (1) The present application synthesizes controllably degradable polylactic acid with borate as a breaking point, wherein the borate is sensitive to water and alkaline conditions and is easily broken under the influence thereof. Degradation experiments show that the borate breaks before the polylactic acid main chain, solving the problem of the control step in the polyester degradation process and effectively accelerating the degradation of polylactic acid.
[0024] (2) The controllably degradable polylactic acid prepared by the present application can adjust the density of the borate breaking point by adjusting the molecular weight of the polylactic acid diol, thereby adjusting the degradation rate of the polylactic acid.
[0025] (3) The present application uses low molecular weight polylactic acid as a raw material, introduces an accelerated degradation group through isocyanate chain extension reaction, and the method is simple, flexible, and has strong designability, and can adapt to industrial scale production. BRIEF DESCRIPTION OF DRAWINGS
[0026] Figure 1 NMR spectrum of the diol chain extender monomer containing borate units in Example 1
[0027] Figure 2 NMR spectrum of PLA-B in Example 3
[0028] Figure 3 Film prepared by hot pressing in degradation examples 3, 6, and 9
[0029] Figure 4 Photo of degradation examples 3, 6, and 9
[0030] Figure 5 M of PLA-B and the comparative sample in degradation examples 1, 4, and 7 increases with the increase of the degradation timew Plot of change in rate of decrease
[0031] Figure 6 M of PLA-B in degradation examples 2, 5, 8 and comparative samples as degradation time increases w Plot of change in rate of decrease
[0032] Figure 7 M of PLA-B in degradation examples 3, 6, 9 and comparative samples as degradation time increases w Plot of change in rate of decrease
[0033] Figure 8 NMR spectra of PLA-B in example 3 before degradation and after 2 days of degradation DETAILED DESCRIPTION
[0034] The application is further illustrated below in conjunction with examples.
[0035] Test method description:
[0036] 1. Determine the successful preparation of borate-containing diol monomer and PLA-B by nuclear magnetic hydrogen spectrum;
[0037] 2. Show the morphological changes of PLA-B and comparative samples during degradation by degradation pictures;
[0038] 3. Test the molecular weight of degradation products of PLA-B and comparative samples during degradation by GPC;
[0039] 4. Determine the structure of PLA-B degradation products by nuclear magnetic hydrogen spectrum;
[0040] The application is further illustrated below in conjunction with examples.
[0041] The polylactic acid diols and triols in the experiment come from Anhui Fengyuan Biotechnology Co., Ltd., 1,2,6-hexanetriol, 1,4-phenyldiboronic acid, 1,8-octanediol, isophorone diisocyanate, and dibutyltin dilaurate come from Adamas, and hexamethylene diisocyanate comes from Macklin.
[0042] Example 1
[0043] Synthesis of borate-containing diol monomer
[0044] Weigh 7.379 g (0.055 mol) of 1,2,6-hexanetriol in a single-necked flask, add 20 mL of anhydrous tetrahydrofuran, and magnetically stir to completely dissolve. Add 4.376 g (0.0264 mol) of 1,4-benzene diboronic acid, continue stirring until completely dissolved, and then add 15.889 g (0.132 mol) of anhydrous magnesium sulfate and 30 mL of anhydrous tetrahydrofuran. Magnetically stir the reaction at 26°C for 24 h. After the reaction is complete, remove the magnesium sulfate by suction filtration to obtain a filtrate, and dry the filtrate thoroughly to remove the solvent to obtain a diol monomer containing borate ester.
[0045] Synthesis of PLA-B
[0046] (1) Weigh 8 g (0.004 mol) of polylactic acid diol (M n = 2000 g-mol -1 ) in a 250 mL three-necked flask, add 20 mL of tetrahydrofuran, heat, and mechanically stir to completely dissolve. Then add 1.346 g (0.008 mol) of hexamethylene diisocyanate and 0.025 g (0.00004 mol) of dibutyl tin dilaurate diluted with tetrahydrofuran dropwise. Stir the reaction at 50°C under reflux with nitrogen condensation and mechanical stirring for 2 h. (2) After 2 h of reaction, weigh 1.448 g (0.004 mol) of the diol monomer containing borate ester units synthesized in step (1) in a beaker, ultrasonically dissolve with tetrahydrofuran, and add to the system. Raise the temperature to 65°C and react for 4 h. After the reaction is complete, pour the reaction liquid into methanol to precipitate the product and wash three times. Dry the precipitate in a vacuum oven at 60°C to a constant weight to obtain the polymer PLA-B containing borate ester cleavage points.
[0047] Example 2
[0048] Synthesis of diol monomer containing borate ester units
[0049] The same as Example 1.
[0050] Synthesis of PLA-B
[0051] (1) Weigh 8 g (0.004 mol) of polylactic acid diol (M n = 2000 g-mol -1(1) In a 250 mL three-necked flask, add 20 mL of tetrahydrofuran, heat, and mechanically stir until completely dissolved. Then, add dropwise 1.778 g (0.008 mol) of isophorone diisocyanate and 0.025 g (0.00004 mol) of dibutyltin dilaurate diluted with tetrahydrofuran. The mixture is refluxed under nitrogen at 50 °C with mechanical stirring for 2 h. (2) After 2 h of reaction, weigh 1.448 g (0.004 mol) of the diol monomer containing the borate ester unit synthesized in step (1) into a beaker, dissolve it in tetrahydrofuran by sonication, and add it to the system. The temperature is raised to 65 °C and the reaction is carried out for 4 h. After the reaction is completed, pour the reaction solution into methanol to precipitate the product and wash it three times. Dry the precipitate in a vacuum oven at 60 °C to constant weight to obtain the polymer PLA-B containing the borate ester breakage point.
[0052] Example 3
[0053] Synthesis of diol monomers containing borate ester units
[0054] Same as Example 1.
[0055] PLA-B Synthesis
[0056] (1) Take 8g (0.004mol) of polylactic acid diol (M n =2000g·mol -1 (1) In a 250 mL three-necked flask, add 20 mL of tetrahydrofuran, heat, and mechanically stir until completely dissolved. Then, add dropwise 1.453 g (0.00864 mol) of hexamethylene diisocyanate and 0.025 g (0.00004 mol) of dibutyltin dilaurate diluted with tetrahydrofuran. The mixture is refluxed under nitrogen at 50 °C with mechanical stirring for 2 h. (2) After 2 h of reaction, weigh 1.680 g (0.00464 mol) of the diol monomer containing the borate ester unit synthesized in step (1) into a beaker, dissolve it in tetrahydrofuran by sonication, and add it to the system. The temperature is raised to 65 °C and the reaction is carried out for 4 h. After the reaction is completed, pour the reaction solution into methanol to precipitate the product and wash it three times. Dry the precipitate in a vacuum oven at 60 °C to constant weight to obtain the polymer PLA-B containing the borate ester breakage point.
[0057] Example 4
[0058] Synthesis of diol monomers containing borate ester units
[0059] Same as Example 1.
[0060] PLA-B Synthesis
[0061] (1) Take 6g (0.003mol) of polylactic acid diol (M n =2000g·mol -1(1) In a 250 mL three-necked flask, add 20 mL of tetrahydrofuran, heat, and mechanically stir until completely dissolved. Then, add dropwise 2.038 g (0.01212 mol) of hexamethylene diisocyanate and 0.019 g (0.00003 mol) of dibutyltin dilaurate diluted with tetrahydrofuran. The mixture is refluxed under nitrogen at 50 °C with mechanical stirring for 2 h. (2) After 2 h of reaction, weigh 3.302 g (0.00912 mol) of the diol monomer containing the borate ester unit synthesized in step (1) into a beaker, dissolve it in tetrahydrofuran by sonication, and add it to the system. The temperature is raised to 65 °C and the reaction is carried out for 4 h. After the reaction is completed, pour the reaction solution into methanol to precipitate the product and wash it three times. Dry the precipitate in a vacuum oven at 60 °C to constant weight to obtain the polymer PLA-B containing the borate ester breakage point.
[0062] Example 5
[0063] Synthesis of diol monomers containing borate ester units
[0064] Same as Example 1.
[0065] PLA-B Synthesis
[0066] (1) Take 8g (0.004mol) of polylactic acid diol (M n =2000g·mol -1 (1) In a 250 mL three-necked flask, add 20 mL of tetrahydrofuran, heat, and mechanically stir until completely dissolved. Then, add dropwise 1.346 g (0.008 mol) of hexamethylene diisocyanate and 0.025 g (0.00004 mol) of dibutyltin dilaurate diluted with tetrahydrofuran. Reflux the mixture under nitrogen at 50 °C with mechanical stirring for 2 h. (2) After 2 h of reaction, weigh 1.448 g (0.004 mol) of the diol monomer containing the borate ester unit synthesized in step (1) into a beaker, dissolve it in tetrahydrofuran by sonication, and add it to the system. Raise the temperature to 65 °C and react for 6 h. After the reaction is complete, pour the reaction solution into methanol to precipitate the product and wash it three times. Dry the precipitate in a vacuum oven at 60 °C to constant weight to obtain the polymer PLA-B containing the borate ester breakage point.
[0067] Example 6
[0068] Synthesis of diol monomers containing borate ester units
[0069] Same as Example 1.
[0070] PLA-B Synthesis
[0071] (1) Take 10.8g (0.0036mol) of polylactic acid diol (M n =3000g·mol -1) in a 250 mL three-necked flask, 20 mL of tetrahydrofuran was added, heated, and mechanically stirred. After complete dissolution, 1.211 g (0.0072 mol) of hexamethylene diisocyanate and 0.023 g (0.000036 mol) of dibutyltin dilaurate diluted with tetrahydrofuran were added dropwise. The reaction was carried out at 50°C under nitrogen gas condensation reflux with mechanical stirring for 2 hours. (2) After 2 hours of reaction, 1.303 g (0.0036 mol) of the diol monomer containing boronic ester units synthesized in step (1) was weighed in a beaker, dissolved in tetrahydrofuran with ultrasonic, and then added to the system. The temperature was raised to 65°C and reacted for 4 hours. After the reaction was completed, the reaction solution was poured into methanol to precipitate the product and washed three times. The precipitate was dried in a vacuum oven at 60°C to a constant weight to obtain a polymer PLA-B containing boronic ester cleavage points.
[0072] Example 7
[0073] Synthesis of diol monomer containing boronic ester units
[0074] In a single-necked flask, 5.837 g (0.055 mol) of 1,2,4-butanetriol was weighed, 20 mL of anhydrous tetrahydrofuran was added, and it was completely dissolved with magnetic stirring. 4.376 g (0.0264 mol) of 1,4-benzenediboronic acid was added, and after complete dissolution, 15.889 g (0.132 mol) of anhydrous magnesium sulfate and 30 mL of anhydrous tetrahydrofuran were added. The reaction was carried out at 26°C with magnetic stirring for 24 hours. After the reaction was completed, the magnesium sulfate was removed by suction filtration to obtain a filtrate, which was thoroughly dried to remove the solvent to obtain a diol monomer containing boronic ester.
[0075] Synthesis of PLA-B
[0076] (1) 8 g (0.004 mol) of polylactic acid diol (M n = 2000 g·mol -1 ) was taken in a 250 mL three-necked flask, 20 mL of tetrahydrofuran was added, heated, and mechanically stirred. After complete dissolution, 1.211 g (0.0072 mol) of hexamethylene diisocyanate and 0.023 g (0.000036 mol) of dibutyltin dilaurate diluted with tetrahydrofuran were added dropwise. The reaction was carried out at 50°C under nitrogen gas condensation reflux with mechanical stirring for 2 hours. (2) After 2 hours of reaction, 1.303 g (0.0036 mol) of the diol monomer containing boronic ester units synthesized in step (1) was weighed in a beaker, dissolved in tetrahydrofuran with ultrasonic, and then added to the system. The temperature was raised to 65°C and reacted for 4 hours. After the reaction was completed, the reaction solution was poured into methanol to precipitate the product and washed three times. The precipitate was dried in a vacuum oven at 60°C to a constant weight to obtain a polymer PLA-B containing boronic ester cleavage points.
[0077] Example 8
[0078] Synthesis of diol monomer containing boronate unit
[0079] Weigh 6.608 g (0.055 mol) 1,2,5-pentanetriol in a single neck flask, add 20 mL anhydrous tetrahydrofuran, and magnetically stir until completely dissolved. Take 4.376 g (0.0264 mol) 1,4-benzene diboronic acid and add it, continue to stir until completely dissolved, then add 15.889 g (0.132 mol) anhydrous magnesium sulfate and 30 mL anhydrous tetrahydrofuran. Stir magnetically at 26°C for 24 h. After the reaction is completed, remove the magnesium sulfate by suction filtration to obtain the filtrate, and dry the filtrate thoroughly to remove the solvent to obtain the diol monomer containing boronate unit.
[0080] Synthesis of PLA-B
[0081] (1) Take 8 g (0.004 mol) polylactic acid diol (Mn= 2000 g·mol-1) in a 250 mL three-necked flask, add 20 mL tetrahydrofuran, heat, open mechanical stirring, and completely dissolve, then add 1.346 g (0.008 mol) hexamethylene diisocyanate and 0.025 g (0.00004 mol) dibutyltin dilaurate diluted with tetrahydrofuran dropwise. Stir magnetically at 50°C under nitrogen condensation reflux for 2 h. n -1 (2) After 2 h of reaction, weigh 1.336 g (0.004 mol) diol monomer containing boronate unit synthesized in step (1) in a beaker, ultrasonically dissolve with tetrahydrofuran, and then add to the system, and the temperature is raised to 65°C for 4 h of reaction. After the reaction is completed, pour the reaction liquid into methanol to precipitate the product and wash three times. Dry the precipitate in a vacuum oven at 60°C to constant weight to obtain the polymer PLA-B containing boronate cleavage points.
[0082] Comparative example
[0083] Specific process as in example 3, and the diol containing boronate unit in step (2) in the synthesis of PLA-B is replaced by 1,8-octanediol.
[0084] Degradation example 1
[0085] The controllably degradable polylactic acid prepared in example 3 is hot-pressed at 120°C for 5 min to obtain a film with a thickness of 50 μm. This film is immersed in a 20% THF / water solution with pH = 8, and samples are taken at intervals of 2, 9, 16, and 60 days, and the removed samples are naturally air-dried at room temperature before measuring the molecular weight.
[0086] Degradation example 2
[0087] Specific process as in degradation example 1, and the pH value of the degradation solution is changed to 10.
[0088] Degradation Example 3
[0089] The procedure was the same as Degradation Example 1 except that the pH of the degradation solution was changed to 12.
[0090] Degradation Example 4
[0091] The PLA-ODO-PU prepared in the comparative example was hot-pressed at 120°C for 5 min to obtain a film with a thickness of 50 μm. The film was immersed in a 20% THF / water solution with a pH of 8, and samples were taken at intervals of 2, 9, 16, and 60 days. The samples taken were naturally air-dried at room temperature, and the molecular weight was measured.
[0092] Degradation Example 5
[0093] The procedure was the same as Degradation Example 4 except that the pH of the degradation solution was changed to 10.
[0094] Degradation Example 6
[0095] The procedure was the same as Degradation Example 4 except that the pH of the degradation solution was changed to 12.
[0096] Degradation Example 7
[0097] PLA with a molecular weight similar to that of Example 3 was hot-pressed at 150°C for 5 min to obtain a film with a thickness of 50 μm. The film was immersed in a 20% THF / water solution with a pH of 8, and samples were taken at intervals of 2, 9, 16, and 60 days. The samples taken were naturally air-dried at room temperature, and the molecular weight was measured.
[0098] Degradation Example 8
[0099] The procedure was the same as Degradation Example 7 except that the pH of the degradation solution was changed to 10.
[0100] Degradation Example 9
[0101] The procedure was the same as Degradation Example 7 except that the pH of the degradation solution was changed to 12.
[0102] Figure 1 Preparation of the diol monomer (HDB) containing boronic ester in Example 1 1 H NMR spectrum. Among them, 4.62 ppm is the chemical shift of the tertiary carbon hydrogen on the five-membered ring, 4.47 ppm and 3.96 ppm are the chemical shifts of the methylene hydrogen on the five-membered ring, and 3.57 ppm is the chemical shift of the methylene hydrogen directly connected to the hydroxyl group. The peak position and peak area of the nuclear magnetic hydrogen spectrum can correspond to the structure, which confirms the successful preparation of HDB. Figure 2 Preparation of PLA-B in Example 3 1The 1H NMR spectrum shows peaks at 4.42 ppm, 3.95 ppm, and 4.57 ppm, all characteristic peaks of HDB mentioned above. Since HDB is readily soluble in methanol, the appearance of these characteristic peaks is attributed to the successful introduction of the borate ester. The disappearance of the methylene hydrogen peak directly linked to the hydroxyl group in HDB further confirms this.
[0103] Figure 3 The films prepared by hot pressing in degradation examples 3 and 6 were both colorless and transparent, while the film in degradation example 9 was brittle and semi-transparent. (See below.) Figure 4 As shown, the PLA-B film prepared in Example 3 immediately turned white and cracked upon being placed in the degradation solution, and after 1 hour, it had become small white fragments. In contrast, the comparative PLA-ODO-PU and PLA maintained their original morphology after 1 hour, with PLA-ODO-PU showing slight whitening, while PLA showed no change. After 60 days of degradation, the PLA-B in Example 3 had crumbled into powder, while the integrity of the comparative PLA-ODO-PU film was higher than that of the former after 1 hour of degradation. As for PLA, the film color remained consistent with that after hot pressing; it became small fragments because it was too brittle and broke during sampling.
[0104] During the degradation process, samples were taken at intervals for molecular weight testing. Figure 5 , Figure 6 , Figure 7 The figures show the changes in M in PLA-B and the control sample with degradation time in degradation examples 1, 4, 7, 2, 5, 8, 3, 6, and 9, respectively. w The rate of decline changes. Their degradation patterns are similar, with... Figure 7 Detailed explanation follows. Two days after degradation, the weight-average molecular weight of PLA remained essentially unchanged, while the comparative example PLA-ODO-PU decreased by 24%, and PLA-B in Example 3 decreased by 43%. After 60 days of degradation, the weight-average molecular weight of PLA decreased by 10%, the comparative example PLA-ODO-PU decreased by 52%, and PLA-B in Example 3 decreased by 72%. NMR spectroscopy was performed on PLA-B two days after degradation, and the results are as follows... Figure 8 As shown, the characteristic peak of borate ester disappeared, corresponding to a sharp decrease in the molecular weight of PLA-B within 2 days. These results indicate that borate ester breaks down before the polylactic acid backbone in alkaline aqueous solution, and within a certain range, stronger alkalinity favors the breakage of borate ester, thus solving the problem of rate-controlling steps in polyester degradation and effectively accelerating the degradation of polylactic acid. Compared to PLA, the comparative PLA-ODO-PU also degraded, possibly due to the introduction of 1,8-octanediol as a soft segment, which improved the flexibility of the chain segments, reduced crystallinity, and resulted in loose molecular chain packing in the amorphous region, facilitating water molecule penetration.
Claims
1. A boronic ester unit-containing, controllably degradable polylactic acid, characterized by, The structural formula is as follows: Wherein a+b=10-67, c=2-6, d=1-5, e=2-25; R1 is one of the following groups:
2. A method for producing a boronic ester unit-containing, controllably degradable polylactic acid, characterized by, Comprise the following steps: (1) First, 1, 4-benzenediol and 1, 2-diol group containing triol compound is dissolved in a solvent, then anhydrous magnesium sulfate is added, and the reaction is stirred at room temperature; Finally, the anhydrous magnesium sulfate is removed by suction filtration to obtain the filtrate, and the filtrate is dried to obtain the diol monomer containing borate unit; (2) The low molecular weight polylactic acid diol is added to the solvent and mixed, and is completely dissolved under heating in an inert gas protection; The diisocyanate and the catalyst are respectively diluted with a solvent and then added dropwise; After all the addition, the condensation reflux reaction is carried out under mechanical stirring; Then, the diol monomer containing borate unit synthesized in step (1) is added, and the chain extension reaction is carried out, and then the precipitation, washing and drying are carried out to obtain the controllable degradation polylactic acid containing borate unit.
3. The method for preparing the boronic ester unit-containing, controllably degradable polylactic acid according to claim 2, wherein, The structure of the 1, 2-diol group containing triol compound in step (1) is as follows: wherein n = 1-5.
4. The method of producing a boronic ester unit-containing degradable polylactic acid according to claim 2, wherein In step (1), the reaction time is 8-24h; The solvent is one or a combination of two or more of anhydrous tetrahydrofuran, methanol and ethanol; The molar ratio of the addition of 1, 4-benzenediol and 1, 2-diol group containing triol compound is 1:2-2.
1.
5. The method of producing a boronic ester unit-containing degradable polylactic acid according to claim 2, wherein The number average molecular weight of the low molecular weight polylactic acid diol in step (2) is not more than 5000 g·mol -1 .
6. The method of producing a boronic ester unit-containing degradable polylactic acid according to claim 2, wherein The diisocyanate in step (2) is one of isocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4, 4'-dicyclohexylmethane diisocyanate and 4, 4-methylene bis (isocyanate phenyl) ; The catalyst is dibutyltin dilaurate or stannous octoate, and the solvent is one or a combination of two or more of tetrahydrofuran, toluene, N, N-dimethylformamide and N, N-dimethylacetamide.
7. The method of producing a boronic ester unit-containing degradable polylactic acid according to claim 2, wherein The molar ratio of the low molecular weight polylactic acid diol, diisocyanate, diol monomer containing borate unit and catalyst in step (2) is 1:2-4.98:1-3.98:0.005-0.
013.
8. The method of producing a boronic ester unit-containing degradable polylactic acid according to claim 2, wherein The reaction time of the end-capping is 1h-2h, and the reaction temperature is 50-65℃; The reaction temperature of the chain extension is 60-85℃, and the reaction time is 2h-6h.
9. The boronic ester unit-containing, controlled degradable polylactic acid prepared by the production method according to claims 2 to 7, characterized by, The degradation rate in the alkaline environment with pH≥8 is faster than that of polylactic acid with the same molecular weight, and the degradation rate increases with the increase of borate content.
10. Use of the boronic ester unit-containing, biodegradable polylactic acid prepared by the production method according to any one of claims 2 to 7, characterized in that, It is applied in short cycle environmental protection packaging, seed coating and biological medicine field.
Citation Information
Patent Citations
Polylactic acid based polyurethane elastomer material for medical infusion apparatus and preparation method thereof
CN105175676A
Recyclable polyurethane binder as well as preparation method and application thereof
CN116875258A